The Change in Stress and Anxiety Level Caused by Practicing Dentistry During COVID-19 Pandemic - Ismail, Noor (Jordan Medical Journal, 2021)
Objectives: The aim of this study is to investigate the change in stress and anxiety level caused by practicing dentistry during COVID-19 pandemic, along with any financial impact and changes in dentists’ cross infection control methods and history taking.Methods: An online questionnaire was conducted between June 10th and 2nd of July 2020 which was distributed after the ease of the lockdown on the dental health sector in most countries. It consisted of four sections (demographic and general characteristics, financial, cross infection control, psychological and mental aspects).Results: The questionnaire was completed by 480 dentists. Participants who were financially affected by the lockdown formed 87.5% of the full sample. There was an increase in the amount of stress they felt in the workplace after the pandemic, and a mean score of (7.1/10) for how much they worry about getting infected by COVID-19 while practicing dentistry. The female dentists had significantly higher stress level than the male dentists after the pandemic (P = 0.001) and significantly higher score for how much they worry about getting infected by Covid-19 while practicing dentistry (P = 0.002).Conclusion: The COVID-19 pandemic made practicing dentistry more stressful than before along with fear of getting infected. Dentists who participated in this study are implementing more methods to prevent getting infected by COVID-19, which could be a positive effect if this level of care remains after the pandemic is over.